Are the fractions difficult? A case study at Elementary School 033 Asmi - Sartono, Sartono; Karso, Karso (International Conference on Elementary Education, 2020)
Mathematics was a subject that was required to all students, especially students in elementary schools. Mathematics was the foundation to understand and develop technology and science. One of the materials in mathematics was fractions. The material was material that was considered as the difficult material to be understood by students. The research design used in this study was a qualitative research design with the case study as its methodology. The results showed that (1) students who met the criteria standard were only 14.29%, i.e. 4 of 28 students. Whereas 85.71% was under the criteria, i.e. 24 of 28 students; (2) the difficulties learners in understanding and resolving a matter of fractions was multiplication of fractions with 29% who answered correctly, meeting fractions and integers with 21.4% who answered correctly, and mixed fractions with 39.3% who answered correctly. From these results, we can say that fractions were a difficult material to be understood by students